Populer Learning Theory : Collaborative Learning: Array - Fuad Mimhamimdala; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
Education is an integrated effort to create an educational environment in which students can actively develop their potential for religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. To create an environment that encourages students to explore and develop themselves, methods need to be in line with the vision of education-one of which is the collaborative learning method. Collaborative learning is a type of learning that allows small groups of people to work together to achieve a common goal. By doing this, they learn skills related to teamwork and social interaction. The method used is literature study, which is a type of research based on reading. The purpose of a literature study is to gather as much information as possible about a particular topic or issue